Answer: <em>Each person runs 3 miles</em>
Step-by-step explanation:
The race is 12 miles long, so you would substitute it for m.
This would make your equation 12/4, which is equal to 3
The geometric rule for the nth term of the geometric sequence for which a1 =−6 and a5=−486 is -6 × 3^(n - 1)
<h3>The nth term of a geometric sequence</h3>
First term, a1 = -6
Fifth term, a5 = -486
a5 = ar^(n - 1)
-486 = -6 × r^(5-1)
-486 = -6r⁴
r⁴ = -486 / 6
r⁴ = 81
r = 4√81
r = 3
Geometric rule:
nth term = ar^(n-1)
nth term = -6 × 3^(n - 1)
Learn more about geometric sequence:
brainly.com/question/24643676
#SPJ1
Answer:
6/8
Step-by-step explanation:
y^1-y^2/x^1-x^2
2+4/2+6
6/8
I know that B is orthographic.
D is isometric.
A is a net.
C is none.
Answer:
<em>a:b:c=8:12:15</em>
Step-by-step explanation:
<u>Combined Ratio</u>
We are given the ratios:
a:b=2:3
b:c=4:5
The combined ratio a:b:c will include all three variables in one single expression.
Before finding it, we must have a common number for the common variable (b). Since b is 3 in the first ratio and 4 in the second ratio, we must equate both by finding the LCM of 3 and 4=12, thus both ratios will be amplified as follows:
a:b=2:3=(2*4):(3*4)=8:12
b:c=4:5=(4*3):(5*3)=12:15
Now there is a common factor in both ratios, we can combine them removing the common factor:
a:b:c=8:12:15